The effect of rewards and achievement motivation on teachers’ performance - Sri Fitria Ningsih; Yasir Arafat; Mulyadi Mulyadi (JPGI (Jurnal Penelitian Guru Indonesia), 2021)
This study aimed to determine: (1) the effect of reward on teachers’performance at state junior high schools of Babat Supat District; (2) the effect of achievement motivation on teachers’ performance atstate junior high schools of Babat Supat District; and (3) the effect of reward and achievement motivation on teachers’ performance atstate junior high schools of Babat Supat District. The data in this study were collected through distributing questionnaires to respondents. The results of filling out the questionnaire were analyzed by using multiple regression analysis through t test, F test, and determination coefficient test. The population in this study were all state junior high schoolsteachers at Babat Supat District, totaling 134 people. The sampling technique used in this study was probability sampling by using Slovin formula to obtain 100 teachers as the research sample. The results of the study found that: (1) there was an effect of reward on teachers’performance at state junior high schools of Babat Supat District; (2) there was an effect of Achievement Motivation on teachers’performance at state junior high schools of Babat Supat District; (3) there was aneffect of reward and achievement motivation simultaneously on teachers’ performance at state junior high schools of Babat Supat District.